Application of the Science, Technology, Engineering, and Mathematics (STEM) Approach Assisted by PhET Simulation to Improve Junior High School Students' Science Process Skills on Atomic Structure Material (Jurnal Inovasi Pendidikan Kimia, 2025)
Student science process skills at Junior High School in several regions in Indonesia were still on low category. This research aimed the finding out science process skills of Junior High School students taught by using Science, Technology, Engineering, and Mathematics (STEM) approach with PhET Simulation. Quasi-Experiment method was used inthis research with nonequivalent control group design. All the ninth-grade Junior High School students were the population of this research. Purposive sampling technique was used in this research, and the samples were the ninth-grade students of class 1 as the experiment group and the students of class 2 as the control group. Collecting data was done by using science process skill test question and observation sheet. The data of student science process skill posttest result were analyzed by using Mann Whitney test with SPSS 22, and the result was 0,001. The findings showed that there was a significant difference of science process skills between students taught by using STEM approach with PhET Simulation and those who were taught by using scientific learning on atomic structure lesson at the ninth grade Junior High School students. N-gain test in the experiment group showed that the result was 0,50 with moderate category.